Janus kinase inhibitors in autoimmune bullous diseases - Huang, Dawei; Zhang, Yuexin; Kong, Luyang; Lu, Jiajing; Shi, Yuling (Frontiers in Immunology, 2023)
Autoimmune bullous disease (AIBD) is a severe skin disorder caused by autoantibodies that target intercellular or cell-matrix adhesion proteins. Currently, the preferred treatment for AIBD involves the use of glucocorticoids or traditional immunosuppressants. Additionally, the utilization of biological agents such as rituximab, omalizumab, and dupilumab is on the rise. However, effectively managing AIBD remains a challenge. The Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway has been implicated in various inflammatory diseases. In recent years, a range of drugs known as JAK inhibitors, which target this pathway, have been developed. Several studies have explored the efficacy and safety of JAK inhibitors for treating AIBD. Consequently, this review begins by examining the role of the JAK/STAT pathway in AIBD, summarizing the application of different JAK inhibitors in AIBD treatment, and emphasizing the importance of disease management in treating AIBD with JAK inhibitors. Furthermore, it highlights the need for a better understanding of the JAK/STAT pathway’s role in AIBD, as well as the effectiveness and safety of JAK inhibitors for treating this disease.